Effects of 8 days intake of hydrogen-rich water on muscular endurance performance and fatigue recovery during resistance training - Zhou, K.; Yuan, C.; Shang, Z.; Jiao, W.; Wang, Y. (Frontiers in Physiology, 2024)
Background: Exercise-induced oxidative stress and inflammation can impair muscular function in humans. The antioxidant and anti-inflammatory properties of molecular hydrogen (H2) highlight its potential to be as an effective nutritional supplement to support muscular function performance in healthy adults. However, the effects of H2 supplementation on muscular endurance performance in trained individuals have not been well characterized. This study aimed to assess the effects of intermittent hydrogen-rich water (HRW) supplementation before, during, and after resistance training on muscular endurance performance, neuromuscular status, and subjective perceptual responses after a 48-h recovery period.